"A Devil and Her Deeds": Charlotte Lamb and the Murders of Trimbelle, Wisconsin - Reneson, Kaitlyn (My University, 2013)
Charlotte Lamb was a hero and a murderer in the 1800s. She was born in Maine, in the 1830s. Her exact birth date is not specified on the census records. Charlotte married Chancy Lamb becoming his second wife. Together they had three children Oliver, Daniel, and Sarah. Charlotte was a known woman in the late 1800s because she killed her husband, two children, a neighbor, and employer. Originally, her fame started when she saved her children from the Sioux Indians who were on the warpath during the 1860s. Every newspaper depicted Charlotte as a devoted mother who walked forty miles to St. Paul, Minnesota with two young children carrying a sick baby to flee the Sioux Indians. The depiction of Charlotte as a devoted mother fell apart a few years later in 1871 when she murdered those same children, murdered her husband, and killed her neighbor, Irene Hall Ottoman and her employer, Royal Garland. Charlotte no longer fit the depiction of the heroic mother and instead became known as a murderer. Charlotte Lamb was arrested August 31, 1872 and on June 11, 1873 she was charged with murdering Sarah and Orin (Daniel) Lamb, Royal Garland, and Jane Ottoman. Charlotte admitted to the death of those four, but did not admit to her husband's murder. Charlotte Lamb was sentenced to life in the Waupun Prison. Charlotte Lamb was analyzed through modes of religion and gender, which were popular in the 19th century. The media and courts interpreted Charlotte's crimes as a result of insanity and lack of femininity. However, analyzing Charlotte through the modes of gender and religion are not appropriate for her case. It is more beneficial to analyze Charlotte as a sociopath.
Keywords: Lamb, Charlotte, approximately 1830-; Murder--Wisconsin--Trimbelle--Case studies; Women murderers--Psychology